Data for: End-of-production light treatments as a tool for controlling chemical composition of herbs and lettuce - Bergstrand, Karl-Johan (Swedish University of Agricultural Sciences, 2026)
The data material comprises raw data from a series of experiments performed at SLU Alnarp, with chemical analyses performed at HAMK in Finland. The data comprises both biological data and chemical data from plants cultivated in greenhopuses and climate chambers. Explanations for each data set is availbale in each file.

Datamaterialet omfattar excelfiler med rådata från en serie experiment som genomförts vid SLU Alnarp, och där kemiska analyser utförts vid HAMK i Finland. Filerna omfattar både biologiska data (såsom frisk- och torrvikt) hos växter som odlats (dessa data har insamlats vid SLU Alnarp), samt deras kemiska komposition (analyserat hos HAMK) Data innefattar endast numeriska data. Förklaringar till varje dataset finns i respektive fil.
Data för: End-of-production light treatments as a tool for controlling chemical composition of herbs and lettuce
Keywords: HORTICULTURAL PRODUCTS; Vegetable; Grönsak; Cilantro; Koriander; Pak Choi; Pak Choi; Lettuce; Sallat; Herb; Kryddväxt; Plant factory; Växtfabrik; Basil; Basilika; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Horticulture; Trädgårdsvetenskap/hortikultur